Facies architecture and depositional processes influencing carbonate facies belt development along a low-inclined shelf, Huk Formation, Norway, and Komstad Formation, Sweden - Van Hook, James J., author; Egenhoff, Sven, advisor; Stright, Lisa, committee member; Stanley, Michelle, committee member (Colorado State University. Libraries, 2022)
Heterozoan, or temperate to cool water, carbonate successions can provide unique obstacles to establishing a typical depositional model that can be universally applied. Unlike their tropical realm counterparts, these carbonates are typically highly heterogeneous, occurring across a wide range of oceanographic and climatic settings, thus requiring a case-by-case approach to interpret any given depositional system. One such example is displayed in the Middle Ordovician aged Huk Formation of southern Norway, and Komstad Formation of Scania, Sweden. These formations are approximately 8m thick, corresponding to the Baltoscandian "Orthoceratite Limestone." This study aims to explore the depositional processes influencing the facies development along a temperate-water, low-inclined carbonate shelf environment by characterizing and interpreting two formations along the shelf profile representing varying positions along the transect. The Huk Formation consists of the lower Hukodden Member composed of mostly massive wackestone, a middle Lysaker Member composed of interbedded nodular to semi-nodular wackestone and carbonate mudstone, and an upper Svartodden Member composed of mostly massive packstone and some massive wackestone. The Komstad Formation is composed of an informal lower member, composed of mostly massive wackestone, and an informal upper member composed of interbedded nodular and semi-nodular wackestone and carbonate mudstone with some massive wackestone beds. The facies of these formations can be grouped into seven carbonate facies: massive trilobite- and brachiopod-bearing calcareous mudstone (facies 1), bioturbated carbonate mud-wackestone (facies 2), planar-bedded fossiliferous wackestone (facies 3a), nodular to lenticular fossiliferous wackestone (facies 3b), mud-rich carbonate wacke- to packstone (facies 3c), massive fossiliferous packstone (facies 4a), and fossiliferous carbonate packstone pockets (facies 4b). These facies are ordered by increasing grain size as well as relative grain biodiversity, reflecting an overall increase in energy regime and subsequent decrease in water depth. These facies are further interpreted to represent the various processes and facies development on a low-inclined carbonate shelf, with massive packstones and wackestones occupying the proximal middle shelf environment, thin beds of nodular to semi-nodular wackestone in the distal middle shelf, and carbonate mudstone in the deep shelf environment. Despite the overall decrease in energy regime at depth, the energetic influences on the carbonate facies changes indicate that storms had a prominent impact on their development throughout the succession. This along with the presence of bioturbation and burrowing throughout the succession indicate that even the distal most reaches of this succession was deposited above storm wave base in a well oxygenated and hospitable environment. These formations further reflect a relatively drastic sea-level fall compared to the over- and underlying dark graptolitic shales. Regional sea-level reconstructions identify a largely scale regression during the deposition of these carbonate successions relative to the overlying and underlying graptolitic siliciclastic mudstones, identifying a relative sea-level low point within the middle of the succession at the transition from the Volkhov to the Kunda stage. Paleoenvironmental and paleoclimatic reconstructions of Middle Ordovician Baltoscandia indicate that environmental conditions during this time were generally relatively stable, suggesting that the fine-scale interbedded wackestone and mudstone characteristic of these formations could serve as excellent indicators of the fine- scale climatic and environmental fluctuations.